2021
DOI: 10.1155/2021/8858874
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Generalized Displacement Boundary and Its Analytical Prediction for Ground Movements Induced by Shield Tunneling

Abstract: The process of shield tunnel excavation would inevitably cause surrounding ground movement, and excessive displacement in the soil could lead to large deformation and even collapse of the tunnel. The methods estimating convergence deformation around tunnel opening is summarized. Then, a universal pattern of displacement boundary condition around the tunnel cavity is originally introduced, which is solved as the combination of three fundamental deformation modes, namely, uniform convergence, vertical translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…When the thickness of the shield tail void reaches the threshold value, its effect on the grout pressure is limited. However, some studies have shown that a larger thickness of the shield tail void leads to larger ground settlement [44]. Therefore, the thickness of the shield tail void should be appropriately designed before tunnel construction to avoid extreme ground settlement.…”
Section: Shield Tail Void Thickness Bmentioning
confidence: 99%
See 1 more Smart Citation
“…When the thickness of the shield tail void reaches the threshold value, its effect on the grout pressure is limited. However, some studies have shown that a larger thickness of the shield tail void leads to larger ground settlement [44]. Therefore, the thickness of the shield tail void should be appropriately designed before tunnel construction to avoid extreme ground settlement.…”
Section: Shield Tail Void Thickness Bmentioning
confidence: 99%
“…On the other hand, the maximum ground settlement increases with the tunnel radius [44]. During the construction of large-diameter tunnels, the initial grout injection pressure needs to be increased to provide sufficient grout pressure and control ground settlement.…”
Section: Tunnel Radius Rmentioning
confidence: 99%
“…The horizontal deformation and deformation rate of the surrounding rock at the arch waist and arch foot increased sharply with the vicinity of the excavation face. During the excavation of the cross section, the horizontal deformation of the surrounding rock at the arch waist and foot is constrained, and the decrease of the horizontal deformation rate of the surrounding rock is due to the presupporting effect of the insertion of the shield shell on the excavated soil (Ye et al, 2017;Zhou, et al, 2019;Fang et al, 2021;Tang, et al, 2021). As the shield tail is far away from the research section, the support of the shield shell disappears, resulting in a sharp increase in the horizontal deformation of the surrounding rock Cao et al, 2021).…”
Section: Influence Of Construction On the Horizontal Convergence Defo...mentioning
confidence: 99%
“…As for the underpass construction of nearby existing sensitive buildings, domestic and foreign scholars have carried out a wealth of research work in the field monitoring [3,4], numerical simulation [1,5,6], theoretical analysis [7][8][9][10], and other aspects. For example, Wang [11] studied the advantages and disadvantages of the underpassing scheme of jacking frame culvert and the underpassing scheme of shallow-buried tunnels in the project of Shanxi Yushen Expressway underpassing the Qin Great Wall ruins and pointed out that the shallow-buried underexcavation method can effectively restrain the deformation of the surrounding rock.…”
Section: Introductionmentioning
confidence: 99%